2016
DOI: 10.1371/journal.pone.0158688
|View full text |Cite
|
Sign up to set email alerts
|

Blood Glutamate Levels in Autism Spectrum Disorder: A Systematic Review and Meta-Analysis

Abstract: ObjectiveGlutamate plays an important role in brain development, neuronal migration, differentiation, survival and synaptogenesis. Recent studies have explored the relationship between blood glutamate levels and autism spectrum disorder (ASD). However, the findings are inconsistent. We undertook the first systematic review with a meta-analysis of studies examining blood glutamate levels in ASD compared with controls.MethodsA literature search was conducted using PubMed, Embase, and the Cochrane Library for stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 32 publications
3
46
1
Order By: Relevance
“…Such cellular changes likely impact on the functional organization of cortical microcircuits in autism, also suggested by molecular studies in animals 4,[22][23][24][25]85,86 . These findings collectively support the imbalance in excitation and inhibition of cortical areas in autism 4,9,16,22,87,88 , which have been related to anomalies in cortical neurotransmitter systems [89][90][91][92] and atypical subcortico-cortical interactions with subcortical structures such as thalamus modulating this balance 7,11,24,74,75,93 . Here, we obtained support for perturbations in cortical microcircuit function from a network perspective, by leveraging a biophysically plausible computational model of brain function, which seeks to tune parameters to optimize the link between structural and connectomes 18 .…”
Section: Discussionsupporting
confidence: 70%
“…Such cellular changes likely impact on the functional organization of cortical microcircuits in autism, also suggested by molecular studies in animals 4,[22][23][24][25]85,86 . These findings collectively support the imbalance in excitation and inhibition of cortical areas in autism 4,9,16,22,87,88 , which have been related to anomalies in cortical neurotransmitter systems [89][90][91][92] and atypical subcortico-cortical interactions with subcortical structures such as thalamus modulating this balance 7,11,24,74,75,93 . Here, we obtained support for perturbations in cortical microcircuit function from a network perspective, by leveraging a biophysically plausible computational model of brain function, which seeks to tune parameters to optimize the link between structural and connectomes 18 .…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, we performed oxylipin analysis of blood and brain regions from juvenile offspring. Moreover, we measured levels of N-methyl-D-aspartate receptor (NMDAR)-related amino acids in the blood and brain from juvenile offspring since NMDAR-related amino acids were altered in patients with ASD (33)(34)(35)(36). Third, we performed 16S rRNA analysis and measurement of short-chain fatty acids of fecal samples in juvenile off\spring after maternal glyphosate exposure since abnormal composition of gut microbiota is shown in patients with ASD (36)(37)(38)(39)(40).…”
Section: Significancementioning
confidence: 99%
“…Changes in the abundance of B. vulgatus were associated with the altered cortisol levels, which may be involved in the pathogenesis of ASD through the HPA pathway . In addition, the abundance of B. vulgatus is significantly positively correlated with the levels of Dglutamine and D-glutamate in the guts of children with ASD [M. Wang et al, 2019] and higher plasma glutamate were found in patients with ASD to in controls [Zheng, Zhu, Qu, & Mu, 2016]. Taken together, this suggests that the elevated levels of B. vulgatus may affect this major excitatory neurotransmitter imbalance and thus contribute to the pathophysiology of ASD.…”
Section: Discussionmentioning
confidence: 96%